Utilization of drugs with reports on potential efficacy or harm on COVID‐19 before, during, and after the first pandemic wave. Issue 11 (21st July 2021) - Enners, Salka; Gradl, Gabriele; Kieble, Marita; Böhm, Michael; Laufs, Ulrich; Schulz, Martin
Abstract: Purpose: Conflicting information on potential benefits of drugs as well as reports on hypothetical harm of commonly used drugs in COVID‐19 treatment have challenged clinicians and healthcare systems. We analyzed the change in ambulatory drug utilization before, during, and after the first wave of the pandemic in 2020. Methods: We explored dispensing data of nearly 19 000 pharmacies at the expense of the statutory health insurance funds covering 88% of Germany's population. We analyzed utilization of publicly discussed drugs with conflicting information. Drug utilization as number of packages dispensed per week from January to June 2020, reflecting 314 million claims, was compared with 2019. Results: Utilization of hydroxychloroquine increased +110% during March 2020 and then slightly decreased until week April 13–19. Renin–angiotensin–aldosterone system inhibitors and simvastatin/atorvastatin increased, +78% and +74%, respectively, and subsequently decreased below 2019 levels. Utilization of azithromycin and all systemic antibiotics decreased continuously from March 2–8 until June to levels considerably lower compared to 2019 (June 22–28: azithromycin: −55%, all systemic antibiotics: −27%). Pneumococcal vaccines utilization initially increased +373%, followed by supply shortages. Paracetamol utilization showed an initial increase of +111%, mainly caused by an increase of over‐the‐counter dispensings. Conclusions: Apart from the pandemic itself, the data suggest that dissemination of misinformation and unsound speculations as well as supply shortages influenced drug prescribing, utilization, and purchasing behavior. The findings can inform post‐pandemic policy to prevent unfounded over‐ and underprescribing and off‐label use as well as drug shortages during a public health crisis.